Getting Out: Political asylum, sexual minorities, and privileged visibility. (December 2014) - Shuman, Amy; Hesford, Wendy S
As part of an emerging field of films documenting the obstacles faced by sexual minorities fleeing persecution and seeking political asylum, the film Getting Out documents both the persecution of sexual minorities in Uganda and the obstacles individuals face in their attempts to get political asylum in South Africa. Using the film as a springboard, we assess the larger issues of recognition, visibility, hypervisibility, and performativity in encounters between sexual minorities, their advocates, and political asylum officials. The rhetorical power of Getting Out lies in its performative staging of LGBTQI asylum seekers' navigation of often competing cultural and legal logics on sexuality. The film calls attention to profound contradictions in the political asylum system for sexual minorities and for any others who challenge the normativity of a social group.